Placebo Effects on Visual Food Cue Reactivity: An Eye-Tracking Investigation - Potthoff, Jonas; Jurinec, Nina; Schienle, Anne (Frontiers in Psychiatry, 2019)
Background: Enhanced visual food cue reactivity has been associated with overeating and weight gain. Due to the increasing prevalence of high-fat food images that we are constantly exposed to in both the real and the virtual world, methods that are able to reduce the reactivity to these types of cues are urgently needed. This eye-tracking study investigated whether food cue reactivity, especially toward high-caloric food, can be reduced with a placebo intervention. Method: Fifty-two women (mean BMI = 23.5) were presented with pictures depicting combinations of food (high-caloric, low-caloric) and non-food items, which were shown once with and once without a placebo in a repeated measures design. The placebo was a pill introduced as a medication targeting peptide YY that is able to reduce appetite specifically for high-caloric food. Gaze data (dwell time, fixations) and self-reported appetite were assessed during the two eye-tracking sessions (with/without placebo). Results: The placebo reduced general appetite as well as specific appetite for the depicted food items. Additionally, the placebo decreased the percentage of fixations and dwell time on the food images. The placebo was not able to specifically change visual food cue reactivity to high-caloric stimuli but reduced responses to both high-caloric and low-caloric food. Reported appetite reduction and weight concerns were positively associated with the placebo-related decrease in visual attention for food. Conclusions: The placebo was able to reduce visual food cue reactivity. This finding demonstrates that placebos are able to alter early visual-attentional processes.